Dasar Dasar History Sistem Pendidikan Nasional - Artino Nanda Bagus Setiawan; Binti Maunah (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2024)
National education is a method that stands on a foundation imbued with the nation’s philosophy of life which has the aim of serving national ideals and the ideals of a nation. Like the education system during the Hindu-Buddhist era. The education system during the Hindu-Buddhist era was based on goals such as religion. Meanwhile, the education system during the Dutch East Indies era was a form of hierarchy between natives and Dutch. The aim of this research is to determine the differences between the education system during the Dutch East Indies period and the Hindu-Buddhist period. The method used is literature study or literature review. The research results show that the goals of the education system during the Dutch East Indies era were also different from those during the Hindu-Buddhist era. Research results: Education during the Dutch East Indies era placed more emphasis on worldly matters and creative abilities in order to obtain superior human resources. Therefore, education today is expected to have the role of teachers in the Hindu-Buddhist era, especially in the context of the special specifications that monks had as teachers. This can include an analysis of qualifications, teaching methods, and their influence on educational developments at that time. This research contribution provides better insight into the development of education in the past as well as valuable lessons for the development of the education system in the future.